2013
DOI: 10.1002/jcb.24556
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of miR‐181a in cartilage metabolism

Abstract: Micro RNA (miRNA) is a small non-coding post-transcriptional RNA regulator that is involved in a variety of biological events. In order to specify the role of miRNAs in cartilage metabolism, we comparatively analyzed the expression profile of known miRNAs in chicken sternum chondrocytes representing early and late differentiation stages. Interestingly, none of the miRNAs displaying strong expression levels showed remarkable changes along with differentiation, suggesting their roles in maintaining the homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 29 publications
(39 reference statements)
0
40
0
Order By: Relevance
“…However, recent studies performed in chondrocytes isolated from chicken sternal cartilage show that miR-181a reduces the expression of COL2A1 (22). Gabler et al showed that the expression of miR-181a is increased during hypertrophic chondrocyte differentiation in human mesenchymal stromal cells treated with transforming growth factor-β (23).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies performed in chondrocytes isolated from chicken sternal cartilage show that miR-181a reduces the expression of COL2A1 (22). Gabler et al showed that the expression of miR-181a is increased during hypertrophic chondrocyte differentiation in human mesenchymal stromal cells treated with transforming growth factor-β (23).…”
Section: Discussionmentioning
confidence: 99%
“…In chicken CCN1, a coding segment on the mRNA supports the expression of CCN1 by facilitating ribosomal recruitment (79). Another report suggests that miR-181a represses CCN1 at a posttranscriptional stage of gene expression, which is mediated by a region outside of the 3′-UTR (80). Progress in similar research on other CCN family members will clarify the solid contribution of miRNAs to the regulation of the CCN family genes.…”
Section: Transcriptional and Posttranscriptional Regulation Of Ccn Famentioning
confidence: 96%
“…Mir-181a represses expression of Ccna2 (encoding for cyclin A2) and Acan . The regulation of these chondrocyte genes by miR-181a may act as a negative feedback for cartilage homeostasis [47]. Another study in chicken cells found that miR-221 was increased upon inhibition of chondrocyte differentiation [48].…”
Section: The Role Of Mirnas In Chondrocytesmentioning
confidence: 99%